ASSESSMENT OF DAMAGE CAUSED BY POLLUTION OF WATER BODIES (Journal of Science-Innovative Research in Uzbekistan, 2024)
In nature, we are witnessing an increase in pollution of water bodies as a result of atmospheric pollution and water depletion. Liquid chemical substances and heavy metals are observed in water bodies. Pollution of water bodies in Khorezm region was assessed and studied